Marketing Mix Relationship with Patients' Re-Visit Interest of Out Patient in Internal Polyclinic at Gunungtua Hospital - Tiasa Pohan; Risandi Mulia (PT Inovasi Pratama Internasional, 2023)
The marketing mix is ​​a set of marketing tools that a company uses to continuously achieve its marketing objectives which consist of product, price, place and promotion. Interest in revisiting behavior that appears in response to objects that indicate the desire of the customer to make repeat visits. The purpose of this study was to analyze the relationship between marketing and patient re-visit interest in outpatient disease polyclinic at Gunungtua Hospital, Padang Lawas Utara Regency in 2020. This type of quantitative research uses a cross sectional approach. The study sample was 150 people with purposive sampling. Data analysis used the chi square test with a significance level of α = 0.05 (95%). The results of the research were supported by the marketing mix associated with the interest in revising products (p = 0.002 <α 0.05), price (p = 0.001 <α 0.05), place (p = 0.002 <α 0.05), and promotion ( p = 0.002 <α 0.05). The results of this study indicate that the marketing mix in the form of products, places, prices and promotions can increase the interest of outpatient re-visits in internal medicine polyclinics. Gunungtua Hospital can improve the marketing mix program so that the interest in patient re-visits increases.